The Development of a Logic Model to Guide the Planning and Evaluation of a Navigation Center for Children and Youth with Complex Care Needs. Issue 4 (1st October 2020) - Luck, Kerrie E.; Doucet, Shelley; Luke, Alison
Abstract: Most systems across health settings and sectors are not well integrated and do not provide the needed supports, resources, or access caregivers and families require to properly care for their child with complex care needs (CCNs). NaviCare/SoinsNavi is a research-based navigation center aimed to help facilitate more convenient and integrated care to support the needs of children, youth, and their families using a patient navigator to offer personalized family-centered care. A logic model was developed by the NaviCare team to facilitate the foundational work needed for a successful program, such as program planning; establishing program goals and objectives; as well as providing a logical illustration of how the program will work. This visual representation of the assumed cause-and-effect connections between program components and desired outcomes informed the identification of inputs, activities, and outputs deemed critical for successful program execution, and for the research and evaluation of the program processes, as well as the program as a whole. This provided a safeguard to ensure critical activities were not overlooked, allowed the comparison of the ideal versus the realities of the program, enhanced communication, and highlighted data and resources that are needed for program implementation and evaluation. This article describes the development of NaviCare/SoinsNavi's logic model, including how this framework will be used to guide the planning and evaluation of the navigation center to support achieving its vision that every child and youth with CCNs have access to the required health, social, and education services they require in a timely manner.